Wide angular range dynamic projection mapping method applied to drone-based avatar robot. (3rd June 2021) - Higuchi, Shino; Oku, Hiromasa
Abstract : In this study, we propose a method for dynamic projection mapping on a target moving at high speed in a wide area around the projection equipment, using a high-speed gaze control system called Saccard Mirror 3. The prototype system successfully projected images over a wide angular range using a rotating mirror and kept projecting images on a flying drone while allowing the drone to move over a wide area. We also demonstrated an avatar robot using a drone based on the proposed system in combination with a teleconference system. This application is important for improving the quality of new normal (QoNN) in the sense that it will enable remote work for customer service in a variety of stores in the future. GRAPHICAL ABSTRACT: UF0001